PENGARUH DEBT TO EQUITY RATIO DAN FIRM SIZE TERHADAP NILAI PERUSAHAAN DENGAN RETURN ON EQUITY SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX (JII) PERIODE 2016-2018 - Indah Khairunnisa; Mismiwati Mismiwati; Bunga Mar’atush Shalihah (I-Finance Journal, 2020)
The Study investigated the influence of Debt to Equity Ratio and Firm Size on Firm Value with Return On Equity as intervening variables in Jakarta Islamic Index (JII) in 2016-2018. This study uses two independent variables that Debt to Equity Ratio and Firm Size. The dependent variables used in this study is the Company Value with indicators of Price to Book Value. While the intervening variable used in this study is Return On Equity. The result showed that there was a positive and significant effect Debt to Equity Ratio on Return On Equity. There was a negative and not significant Firm Size on Return On Equity. Debt to Equity Ratio has no significant effect on Firm Value. Firm Size has no significant effect on Firm Value. There wasa positive and significant effect Return On Equity on Firm Value. Return On Equity is mediating the effect of Debt to Equity Ratio on Firm Value (Partial Mediation). Return On Equity is mediating the effect of Firm Size on Firm Value (Partial Mediation).